Narración de cuentos y su impacto en el desarrollo del lenguaje en niños de Educación Inicial I - Santillan Zambrano, Celida Adriana (2025)
The objective of this research is to determine the impact of storytelling on the language development of children in Early Childhood Education sublevel I at the “Ana Rosa Valdiviezo de Landívar” Educational Unit. The problem arises from the observation of linguistic difficulties in children such as poor pronunciation and limited vocabulary. In addition, the family environment in some cases encourages the use of signs instead of verbal communication, which limits language development in infants. The study is aligned with the mixed approach and the techniques: observation, interview and survey suitable to acquire a comprehensive determination of the study. The results show that storytelling positively impacts language development in children in Early Childhood Education I, supported by the positive considerations of parents and the structured implementation of the teacher. Children when exposed to this strategy improve vocabulary and pronunciation, strengthen oral comprehension and expression.